Inclusive Education / Edited by Harry Daniels and Philip Garner ; series editor: Crispin Jones - Daniels, Harry, editor 344732; Garner, Philip, editor 550447 (London : Kogan Page ; Sterling, Va. : Stylus Pub.)
Inclusive education" is the term now used to describe the incorporation of special needs into mainstream education. This selection of papers provides perspectives and dialogue on inclusive education from around the world, defining the philosophical, political and educational implications.